2016
DOI: 10.11591/.v5i1.4765
|View full text |Cite
|
Sign up to set email alerts
|

Association between Non-Cigarette/Smokeless Tobacco and Hypertension in the National Health Interview Survey: A Pseudo-Panel Analysis

Abstract: This study sought to examine assumption between having ever used noncigarette tobacco or smokeless tobacco, and a diagnosis of hypertension among a sample of 13, 086 United States adults participating in the National Health Interview Series from 2012-2014. A pseudo-panel analysis of data extracted from the Integrated Health Interview Series Survey was conducted. The generalized linear mixed model was used to quantify the effect of a history of non-cigarette tobacco, smokeless tobacco, and socio-demographic pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Of 15 studies reporting on SLT-product data from USA [ 10 14 , 42 50 , 53 ], eight were exclusively in USA [ 42 46 , 48 50 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of 15 studies reporting on SLT-product data from USA [ 10 14 , 42 50 , 53 ], eight were exclusively in USA [ 42 46 , 48 50 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…A ‘poor’-rated meta-analysis reported no association between SLT-products and stroke in US data [ 11 ]. A US cross-sectional study reported lower self-reported hypertension (OR = 0.88; 95% CI 0.79–0.98) in SLT-product users (adjusted for smoking status and duration) [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…The pseudo-panel data approach is actually a solution to transform the individual-level cross-sectional data into the group-level data (i.e., pseudo-panel data)such that the typical longitudinal models can be applied to e ciently and consistently estimate the change of the interested outcome variable over time. [13] This approach has been increasingly applied to public health [14,15] . According to the methods described in the literature [16,17], we constructed two pseudo-panel datasets from our discovery and replicate data by grouping three time-invariant variables -gender, birth year, and blood donation history.…”
Section: Construction Of Pseudo-panel Datasetsmentioning
confidence: 99%
“…Our study was actually an observational study using pseudo-panel approach to analysis the data [13][14][15]. Thus, we used the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) statement to ensure standardisation and enhance the quality of the reporting [18].…”
Section: Construction Of Pseudo-panel Datasetsmentioning
confidence: 99%
See 1 more Smart Citation